Sabrina Soto Home Design : A Layer-by-layer Approach to Turning Your Ideas into the Home of Your Dreams - Soto, Sabrina (Hoboken, N.J. : John Wiley & Sons, 2012)
A step-by-step design process from choosing colors, selecting surface treatments, integrating storage to organize your space, editing your furniture, picking colors, illuminating your design, and finally adding accents.--
The first layer : understand your space and plan your design -- The second layer : choose your colors -- The third layer : select your surface treatments -- The fourth layer : integrate storage to organize your space -- The fifth layer : edit your furniture -- The sixth layer : select your textiles -- The seventh layer : illuminate your design -- The eighth layer : accent your interior design -- A never-ending adventure.
Includes index.
Keywords: Interior decoration